17, 20-Epoxysteroids from octocoral Isis hippuris (Linnaeus, 1758). (12th October 2022) - Huang, Yi-Qi; Chen, Po-Jen; Yang, San-Nan; Chien, Su-Ying; Zheng, Li-Guo; Wen, Zhi-Hong; Kuo, Liang-Mou; Sung, Ping-Jyun
Graphical abstract: Highlights: 17, 20-epoxysteroids, hippuristeroketal B (1 ), hippuristerones A (2 ) and I (3 ), were isolated from octocoral Isis hippuris . The absolute stereochemistry of steroids 1 –3 was determined by single-crystal X-ray diffraction analysis. Hippuristerone A (2 ) exhibited cytotoxic effect against HT-29 and DLD-1 cancer cells. Abstract: Three 17, 20-epoxysteroids, including a new metabolite, hippuristeroketal B (1 ), as well as two known compounds, hippuristerones A (2 ) and I (3 ), have been isolated from octocoral Isis hippuris collected off the waters of Taiwan. The structure of steroid 1 was deduced by extensive 1D and 2D NMR studies. The absolute stereochemistry of steroids 1 –3 was determined by single-crystal X-ray diffraction analysis. Steroid 2 exhibited cytotoxic effect against HT-29 and DLD-1 cancer cells with IC50 values of 11.39 and 12.86 μM, respectively.